Laparoscopic Management of Renal Hydatid Cyst - Aggarwal, Sandeep (Society of Laparoendoscopic Surgeons, 2014)
INTRODUCTION: Renal involvement by hydatid disease is uncommon. The patients may be asymptomatic or present with flank pain, hematuria, and hypertension. Surgery is the mainstay of treatment, and options include cyst deroofing, partial nephrectomy, and total nephrectomy. We share our experience of laparoscopic management of 3 patients with large hydatid cysts of the kidney and review the literature. CASE DESCRIPTION: Three patients with hydatid cysts of the kidney were treated at our institution between 2008 and 2010. In all 3 patients, hydatid disease involved the left kidney. One of the three cases also had concomitant liver involvement. Abdominal pain was the predominant symptom. A flank mass was palpable in 2 patients. The diagnosis was confirmed on abdominal ultrasonography and computed tomography in all 3 patients. Laparoscopic management was successfully completed in 2 patients. A large intrahepatic cyst in 1 patient prompted conversion to an open procedure. A special hydatid trocar-cannula system helps in eliminating the possibility of spillage from the cyst while puncturing and aspirating the cyst. DISCUSSION: There are few reports on laparoscopic management of this uncommon disease of the kidney. In our series the laparoscopic management was attempted in all 3 cases. The procedures included laparoscopic aspiration of the cyst contents along with subtotal excision of the ectocyst in 2 patients and nephrectomy in 1 patient. The latter case had to be converted to an open procedure because of inaccessibility of the intrahepatic liver hydatid cyst. Laparoscopic management of renal hydatid cysts is feasible and safe.